2001
DOI: 10.1007/pl00002396
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant versus Neoadjuvant Radiochemotherapy for Locally Advanced Rectal Cancer A Progress Report of a Phase-III Randomized Trial (Protocol CAO/ARO/AIO-94)

Abstract: The patient accrual of our trial is satisfactory, neoadjuvant radiochemotherapy is well tolerated and bears no higher risk for postoperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 25 publications
0
54
1
7
Order By: Relevance
“…Clinical trials commonly report physiciangraded diarrhea, which may not fully capture the QOL effects from the patient's perspective and may underrepresent the true prevalence of this symptom. Although previous studies have reported an approximately 30% rate of physician-reported, acute, grade 2 to 5 diarrhea, [1][2][3]5 in clinical practice, it is observed more commonly. In addition, other treatment-related, acute GI symptoms are observed frequently in the clinic but are not described well in the literature.…”
Section: Original Articlementioning
confidence: 78%
“…Clinical trials commonly report physiciangraded diarrhea, which may not fully capture the QOL effects from the patient's perspective and may underrepresent the true prevalence of this symptom. Although previous studies have reported an approximately 30% rate of physician-reported, acute, grade 2 to 5 diarrhea, [1][2][3]5 in clinical practice, it is observed more commonly. In addition, other treatment-related, acute GI symptoms are observed frequently in the clinic but are not described well in the literature.…”
Section: Original Articlementioning
confidence: 78%
“…However, increased toxicity and a slight increase in early deaths were seen in the preoperative arm. The German CAO/ARO/AIO-94 study showed that preoperative chemoradiation was well tolerated and carried no higher risk of postoperative morbidity, but efficacy data are awaited (Sauer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The potential disadvantage of preoperative CRT is overtreatment of patients either because of early pathological stage (estimated to be 18% in one randomised study (Sauer et al, 2001)) or presence of occult metastatic disease undetected on pretreatment imaging. Preoperative CRT has been used by many oncologists especially in North America for patients with clinical T3 disease based on extrapolated benefits from postoperative CRT and a number of nonrandomised studies demonstrating significant pathological complete response (pCR) rates and acceptable acute toxicity profile with the use of preoperative CRT.…”
mentioning
confidence: 99%
“…The preoperative therapy tended to be more toxic than the postoperative (grade 4/5 toxicity 34% vs. 24%, p0/0.07). A large German trial, presently still recruiting patients, has a similar design (45). The neoadjuvant therapy is well tolerated in the trial and bears no higher risk for postoperative morbidity.…”
Section: Sphincter Preservation After Preoperative Radiationmentioning
confidence: 99%